Constructing Masculine and Feminine Traits: A Social Constructive Reading of Robert Frost’s “Home Burial” - Yaw-kan, Joseph Peter; Gambil, Jonas Naoh Xaxier; Akor, Daniel Yaw; Donwaazum, Mark Kpatiewiizi (Universitas Sanata Dharma, 2024)
Reading Robert Frost’s “Home Burial” from a sociological perspective is a herculean task. Given that this poem by the American poet has received large volumes of critical literary conversation since its publication. Notwithstanding this daunting scholarly task, it is imperative to point out the nuanced representation of gender and the constitutive manifestations reflected thereof. This paper, therefore, examines Frost’s characters and their expression of masculinity and femininity in “Home Burial”. The paper is framed within the social constructivist theory of masculinities proposed by Moynihan (1998). The paper asserts that Frost favors the man/male gender over the woman/female gender in his assessment of how both gender types receive and process emotions, grief, pain, and fear. From the purview of the social constructivists, the paper reveals that there are fixed signifiers for males and females that shape their outlook during social events/contexts such as death. The paper further reveals that the theme of reality (realism) is crucial in 20th-century poetry, explicating its social context and application. The paper is a contribution to the research on Frostian poetry.